Collaborative Mechanisms for Building Innovative E‑Commerce Teaching Teams: A Professional Development Framework for Vocational Colleges - Yang, Pengbo; He, Haonan; Ziyu, Liu (Journal of Research in Vocational Education, 2026)
Considering the distinctive characteristics of the e‑commerce discipline and the corresponding industrial demands, this study explores professional standards for e‑commerce educators within the context of building teaching innovation teams in vocational education. The proposed framework introduces innovations across multiple dimensions, including teaching philosophies, instructional models, content delivery, pedagogical standards, and collaborative teamwork. In tandem, it establishes elevated requirements for teachers’ ideological and political competence, professional ethics, and subject‑specific proficiencies. Aimed at cultivating technically skilled talents capable of meeting the evolving needs of the e‑commerce industry, the study articulates a set of professional standards grounded in the development of vocational education teaching innovation teams. These standards serve to codify the essential qualifications of e‑commerce instructors, promote their sustained professional growth, and ultimately provide robust faculty support for the continuous improvement of talent cultivation quality.